Transforming English Language Learning in Primary Education: Adaptive Strategies for the Digital Era - Bayu Rachman; Ricky Sriyanda (International Journal of Elementary Education, 2025)
Limited access to devices, unstable internet connections, and monotonous digital practices often reduce the effectiveness of English learning in primary schools. This study investigates the application of adaptive digital strategies to improve students’ learning experiences and motivation. A qualitative descriptive design was employed, involving purposively selected teachers and students from upper primary grades. Data were collected through semi-structured interviews and classroom observations, then analyzed thematically to identify challenges, strategies, and required support. The results revealed that interactive media, digital quizzes, and video-based resources increased student engagement and provided immediate feedback that supported comprehension. However, the effectiveness of these strategies was constrained by infrastructure limitations, low digital literacy, and frequent distractions from entertainment applications. The study concluded that adaptive strategies are effective only when supported by stable connectivity, adequate devices, teacher readiness, and parental involvement. The findings highlight the importance of positioning teachers as learning designers and building a supportive digital ecosystem. This study recommends strengthening teacher training, ensuring equal digital access, and promoting family participation as key steps in transforming English learning at the primary school level.